2016
DOI: 10.1007/s11746-016-2810-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tween 20 on the Properties of Stearate Oleogels: an in‐Depth Analysis

Abstract: stress (either thermal or mechanical) was introduced, the strength of the oleogels was decreased due to the syneresis of oil through the pores. An increase in the Tween 20 concentration-dependent relaxation of the oleogels was also observed due to the polymorphic change and arrangement of the gelators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Visual observation of the oleogels suggested that the addition of stearic acid results in oleogels with a homogenous matrix, which can be explained by the formation of mixed crystals when fatty acid-fatty alcohol mixtures are used for structuring of the oils [30]. A slight alteration in the crystal habit completely changes the architecture of the gelator network and hence their texture [13,14]. Microscopic results indicated that stearic acid promoted the formation of long gelator fibers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Visual observation of the oleogels suggested that the addition of stearic acid results in oleogels with a homogenous matrix, which can be explained by the formation of mixed crystals when fatty acid-fatty alcohol mixtures are used for structuring of the oils [30]. A slight alteration in the crystal habit completely changes the architecture of the gelator network and hence their texture [13,14]. Microscopic results indicated that stearic acid promoted the formation of long gelator fibers.…”
Section: Resultsmentioning
confidence: 99%
“…An alteration in the microstructure alters the spaces available in between the gelator network structure. The formation of plate-like structure hinders solute migration [14]. On the contrary, the formation of fiber-like structures promotes solute migration [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations